Detection rates of recurrent prostate cancer: 68Gallium (Ga)-labelled prostate-specific membrane antigen versus choline PET/CT scans. A systematic review. (January 2019) - Moghul, Masood; Somani, Bhaskar; Lane, Tim; Vasdev, Nikhil; Chaplin, Brian; Peedell, Clive; KandaSwamy, Gokul Vignesh; Rai, Bhavan Prasad
Background: The aim of this work was to assess the use of prostate-specific membrane antigen (PSMA)-labelled radiotracers in detecting the recurrence of prostate cancer. PSMA is thought to have higher detection rates when utilized in positron emission tomography (PET)/computed tomography (CT) scans, particularly at lower prostate-specific antigen (PSA) levels, compared with choline-based scans. Methods: A systematic review was conducted comparing choline and PSMA PET/CT scans in patients with recurrent prostate cancer following an initial curative attempt. The primary outcomes were overall detection rates, detection rates at low PSA thresholds, difference in detection rates and exclusive detection rates on a per-person analysis. Secondary outcome measures were total number of lesions, exclusive detection by each scan on a per-lesion basis and adverse side effects. Results: Overall detection rates were 79.8% for PSMA and 66.7% for choline. There was a statistically significant difference in detection rates favouring PSMA [OR (M–H, random, 95% confidence interval (CI)) 2.27 (1.06, 4.85), p  = 0.04]. Direct comparison was limited to PSA < 2 ng/ml in two studies, with no statistically significant difference in detection rates between the scans [OR (M–H, random, 95% CI) 2.37 (0.61, 9.17) p  = 0.21]. The difference in detection on the per-patient analysis was significantly higher in the PSMA scans ( p < 0.00001). All three studies reported higher lymph node, bone metastasis and locoregional recurrence rates in PSMA. Conclusions: PSMA PET/CT has a better performance compared with choline PET/CT in detecting recurrent disease both on per-patient and per-lesion analysis and should be the imaging modality of choice while deciding on salvage and nonsystematic metastasis-directed therapy strategies.